Albania : First Review Under the Extended Arrangement and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2014)
KEY ISSUES Background: On February 28, the Executive Board approved a three-year Extended Arrangement with access of SDR 295.42 million (492.4 percent of quota). A purchase of SDR 23.55 million (about EUR 26.4 million) was made in April 2014, and another will be made in the same amount upon completion of the first review. Recent Economic Developments: Growth in 2013 was the lowest in more than 15 years. The economy is showing tentative signs of recovery, but remains below potential. Successive monetary easing has not prevented credit contraction. The banking system remains stable, but asset quality is a concern. Program Performance and Risks: The program is on track. All end-March quantitative performance criteria and structural benchmarks were met, except for the structural benchmark on contracting an external auditor to conduct risk-based audits of arrears payments, which was not met but the government expects to complete in the coming weeks. An indicative target on accumulation of new arrears was not met although by a small margin and inflation has been slightly below the inner band prescribed under the inflation consultation clause. Program risks emanate from the complexity of reforms, particularly in electricity sector, and the need for sustained political commitment over the medium term. Policy Recommendations: No new fiscal measures will be needed in 2014, but the authorities should tackle emerging fiscal risks. Arrears clearance can be accelerated once external audits have progressed sufficiently. Addressing high NPLs will require continued efforts to clean bank and private sector balance sheets. Preparatory work related to the 2015 budget and structural reforms should start soon.